2018
DOI: 10.1038/s41589-018-0009-4
|View full text |Cite|
|
Sign up to set email alerts
|

Resistance to nonribosomal peptide antibiotics mediated by d-stereospecific peptidases

Abstract: Nonribosomal peptide antibiotics, including polymyxin, vancomycin, and teixobactin, most of which contain D-amino acids, are highly effective against multidrug-resistant bacteria. However, overusing antibiotics while ignoring the risk of resistance arising has inexorably led to widespread emergence of resistant bacteria. Therefore, elucidation of the emerging mechanisms of resistance to nonribosomal peptide antibiotics is critical to their implementation. Here we describe a networking-associated genome-mining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 52 publications
2
65
0
Order By: Relevance
“…A recent study based on global genome mining has demonstrated that many microorganisms harbor D-stereospecific peptidases which are involved in resistance to nonribosomal peptide antibiotics, such as polymyxin, vancomycin, and teixobactin (30). Consistently, daptomyxin and other bacterial cyclic peptides can be degraded by hydrolysis in Streptomyces spp.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study based on global genome mining has demonstrated that many microorganisms harbor D-stereospecific peptidases which are involved in resistance to nonribosomal peptide antibiotics, such as polymyxin, vancomycin, and teixobactin (30). Consistently, daptomyxin and other bacterial cyclic peptides can be degraded by hydrolysis in Streptomyces spp.…”
Section: Discussionmentioning
confidence: 99%
“…Well-known examples of antibiotic destructases include beta-lactamases that hydrolyze the strained 4-membered lactam of beta-lactam antibiotics ( Bush and Jacoby, 2010 ; Brandt et al, 2017 ), and aminoglycoside-inactivating enzymes including phosphotransferases, acetyltransferases, and adenylyltransferases that modify the free amine and hydroxyl groups of aminoglycoside antibiotics ( Ramirez and Tolmasky, 2010 ). Known classes of antibiotic destructases (antibiotic substrates) include peptidases (bogorol, bacitracin) ( Li et al, 2018 ), hydrolases (beta-lactams, macrolides) ( Bush and Jacoby, 2010 ; Morar et al, 2012 ), thioltransferases (fosfomycin) ( Rife et al, 2002 ; Thompson et al, 2013 ), epoxidases (fosfomycin) ( Fillgrove et al, 2003 ), cyclopropanases (colibactin) ( Tripathi et al, 2017 ), acyl transferases (aminoglycosides, chloramphenicol, glufosinate, tabtoxinine-beta-lactam, streptogramin) ( Leslie, 1990 ; Botterman et al, 1991 ; Sugantino and Roderick, 2002 ; Ramirez and Tolmasky, 2010 ; Wencewicz and Walsh, 2012 ; Favrot et al, 2016 ), methyl transferases (holomycin) ( Li et al, 2012 ; Warrier et al, 2016 ), nucleotidylyl transferases (aminoglycosides, lincosamide) ( Morar et al, 2009 ; Ramirez and Tolmasky, 2010 ), ADP-ribosyltransferases (rifamycins) ( Baysarowich et al, 2008 ), glycosyltransferases (aminoglycosides, rifamycins, macrolides) ( Bolam et al, 2007 ; Ramirez and Tolmasky, 2010 ; Spanogiannopoulos et al, 2012 ), phosphotransferases (aminoglycosides, chloramphenicol, rifamycins, macrolides, viomycin) ( Thiara and Cundliffe, 1995 ; Izard and Ellis, 2000 ; Ramirez and Tolmasky, 2010 ; Stogios et al, 2016 ; Fong et al, 2017 ), lyases (streptogramins) ( Korczynska et al, 2007 ), and oxidoreductases (tetracyclines, rifamycins) ( Park et al, 2017 ; Koteva et al, 2018 ). As antibiotic prospecting continues, the list of antibiotic destructases is certain to grow ( Crofts et al, 2017 ; Li et al, 2018 ; Pawlowski et al, 2018 ).…”
Section: Tetracycline Destructasesmentioning
confidence: 99%
“…Qian and coworkers have shown that additional peptidases that likely recognize Nacyl-D-Asn motifs are encoded in cryptic gene clusters. 19 Our fluorogenic probe may be adaptable to these uncharacterized homologs, enabling the direct monitoring of other secondary metabolite pathways. Overall, this work shows how detailed characterization of biosynthetic enzymes can enable the development of innovative tools to interrogate natural products.…”
mentioning
confidence: 99%